Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Bahasa Anak Di TK Bustanul Athfal 5 Sragen Tahun Ajaran 2015/2016 - Pratiwi, Ika Cahya; Sunaryo M. Pd AUD, Drs. Ilham Sunaryo M. Pd AUD (2016)
Pattern proper family education will provide opportunities for children to learn optimally, it implies that the treatment used in the lives of children in the family can help develop the intellect and creativity to think efficiently and effectively to achieve the learning objectives in school. The purpose of this study was to determine the relationship Parenting Parents against children in Kindergarten Language Development Bustanul Athfal 5 Sragen Academic Year 2015-2016. This study took place in kindergarten Bustanul Athfal 5 Sragen with this type of research is descriptive correlational. The population in this study were 63 children, and a sample of 46 children, using simple random sampling. The data used to authoritarian parenting parents and language development using a questionnaire. While data analysis using product moment correlation analysis technique. Based on the results of correlation r_xy = 0.422 (r count> r table) or 0.422> 0.422 at significant level of 0.1% can be concluded that authoritarian parenting parents has a negative correlation to the development of children's language. This indicates that the two variables were not interconnected.